Symmetry and Modern Physics : Yang Retirement Symposium. - Sterman, George; Shrock, R. (Robert); Goldhaber, A.; Smith; Nieuwenhuizen, P.Van; Weisberger, W. (World Scientific, 2003)
C.N. Yang, one of the greatest physicists of the 20th Century, was awarded the Nobel Prize in 1957, jointly with T.D. Lee, for research concerning fundamental physical principles, astounding the world of physics by demonstrating that elementary particles and their reactions discriminate between their left- and right-handed states, a property known as parity nonconservation. With R.L. Mills, he created the concept of non-abelian gauge theories, the foundation of the modern description of elementary particles and forces. Professor Yang has worked on a wide range of subjects in physics, but his enduring concerns have been symmetry principles and statistical mechanics. In 1999, a symposium was held at the State University of New York at Stony Brook to mark the retirement of C.N. Yang as Einstein Professor and Director of the Institute for Theoretical Physics, and to celebrate his many achievements. A noteworthy selection of the papers presented at the symposium appears in this volume in honor of Professor Yang.